(untitled) (The Journal of Knowledge and Innovation, 2024)
The paper analyzes the interconnected nature of individual and collective identities among the Gurkha soldiers in Mike’s The Gurkhas, on the themes of recognition and misrecognition, power dynamics, stereotypes, and exoticization from a decolonial psychoanalytic perspective by Robert K. Beshara. It centers on how recognition, which validates a group’s cultural, social, and historical validity, and misrecognition, which reduces individuals to simplified stereotypes or exoticized notions, impact the Gurkhas for their portrayal. The legacy of colonialism and prevailing beliefs contribute to their simultaneous experience of recognition and misrecognition. Power dynamics further situate the Gurkhas within a structure that perpetuates unequal relationships, casting them as the ‘Other’ or the exotic, distorting their representation, and reinforcing the dominant narratives of the colonizers. Stereotyped narratives and images used as the data in the research portray them as fierce warriors, loyal but lacking agency, originating from admiration but limiting understanding and contributing to the misrecognition of their diverse experiences. The cultural practices and military valor are often romanticized or fetishized in popular media, limiting them to symbols of bravery or curiosity. To truly grasp the Gurkhas’ identity, a reimagining of recognition must be placed at the front, embracing their complexity, agency, and humanity. Exposing unconscious processes and challenging colonial narratives foster genuine recognition that surpasses stereotypes and exoticization, promoting a more comprehensive and equitable representation of the Gurkha soldiers. The research brings awareness to Gurkhas about being exoticized, stereotyped, and misrecognized by the British and helps stakeholders and policymakers rethink the Gurkha recruitment policy in foreign military forces. It also opens up a new avenue for researchers and academicians who are interested in researching Gurkhas serving in the military.